O açaí como ícone de identidade social, econômica e cultural amazônica: um estudo de caso em Igarapé-Miri - SANTOS, Cristiano Moreno Valente dos (Universidade Federal do Pará, 2025)
The açaí berry, a fruit originating from the Euterpe oleracea palm tree, is a staple in the diet of the Amazon region's populations. With its intense color and distinct flavor, this fruit not only nourishes but also carries with it a rich cultural tradition. Its harvesting and processing involve techniques passed down through generations, making açaí a symbol of identity and belonging for the local communities. Thus, this study focuses on the central role that açaí plays in shaping the social, economic, and cultural identity in the Amazon, using the municipality of IgarapéMiri and the community of Santo Antônio as specific case studies. The relevance of açaí in the local economy, as well as its connections with cultural and social practices, are explored to understand its contributions to Amazonian identity. The research combines qualitative and quantitative approaches, including the analysis of existing studies, landscape analysis, questionnaires, typologies, interviews, and participatory observation. In Igarapé-Miri, observations and visits were made to the complex of fairs and the municipal public market Miguel Tourão Pantoja to understand the commercialization and local population's relationship with the açaí fruit. In the community of Santo Antônio, various data collection and analysis activities were carried out, notably the application of questionnaires to local families, observation, and the categorization of production systems into three distinct types, based on the main sources of income and productive arrangements associated with açaí. Thus, in IgarapéMiri, açaí is not just a product for trade; it is a pillar of local identity, a link that connects generations and perpetuates traditions. In the community of Santo Antônio, it is observed that açaí is intrinsic to daily life and community practices, being the main vector for income source, social cohesion, and the transmission of ancestral knowledge.